Brachytherapy for Prostate Cancer: A Systematic Review - Georgios Koukourakis; Nikolaos Kelekis; Vassilios Armonis; Vassilios Kouloulias (Advances in Urology)
Low-dose rate brachytherapy has become a mainstream treatment option for men diagnosed with prostate cancer because of excellent long-term treatment outcomes in low-, intermediate-, and high-risk patients. To a great extend due to patient lead advocacy for minimally invasive treatment options, high-quality prostate implants have become widely available in the US, Europe, and Japan. High-dose-rate (HDR) afterloading brachytherapy in the management of localised prostate cancer has practical, physical, and biological advantages over low-dose-rate seed brachytherapy. There are no free live sources used, no risk of source loss, and since the implant is a temporary procedure following discharge no issues with regard to radioprotection use of existing facilities exist. Patients with localized prostate cancer may benefit from high-dose-rate brachytherapy, which may be used alone in certain circumstances or in combination with external-beam radiotherapy in other settings. The purpose of this paper is to present the essentials of brachytherapies techniques along with the most important studies that support their effectiveness in the treatment of prostate cancer.